2012
DOI: 10.1007/s10295-012-1106-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated organic–aqueous biocatalysis and product recovery for quinaldine hydroxylation catalyzed by living recombinant Pseudomonas putida

Abstract: In an earlier study, biocatalytic carbon oxyfunctionalization with water serving as oxygen donor, e.g., the bioconversion of quinaldine to 4-hydroxyquinaldine, was successfully achieved using resting cells of recombinant Pseudomonas putida, containing the molybdenum-enzyme quinaldine 4-oxidase, in a two-liquid phase (2LP) system (Ütkür et al. J Ind Microbiol Biotechnol 38:1067-1077, 2011). In the study reported here, key parameters determining process performance were investigated and an efficient and easy met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This property allows these strains to grow in the presence of or even produce otherwise toxic chemicals like aromatic phenols and styrenes (Wierckx et al, 2005 ; Verhoef et al, 2009 ; Volmer et al, 2014 ). Furthermore, biocatalysis in biphasic aqueous/organic systems allows direct product removal of hydrophobic biochemicals and could simplify biotechnological processes (Blank et al, 2008 ; Heerema et al, 2011 ; Ütkür et al, 2012 ; Volmer et al, 2014 ). On the other hand, during the recombinant production of, e.g., valuable biodetergents like rhamnolipids (Wittgens et al, 2011 ), the required aeration leads to strong reactor foaming, which is technically hard to handle with conventional antifoam technologies (Küpper et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…This property allows these strains to grow in the presence of or even produce otherwise toxic chemicals like aromatic phenols and styrenes (Wierckx et al, 2005 ; Verhoef et al, 2009 ; Volmer et al, 2014 ). Furthermore, biocatalysis in biphasic aqueous/organic systems allows direct product removal of hydrophobic biochemicals and could simplify biotechnological processes (Blank et al, 2008 ; Heerema et al, 2011 ; Ütkür et al, 2012 ; Volmer et al, 2014 ). On the other hand, during the recombinant production of, e.g., valuable biodetergents like rhamnolipids (Wittgens et al, 2011 ), the required aeration leads to strong reactor foaming, which is technically hard to handle with conventional antifoam technologies (Küpper et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Bühler et al. reported the use of heterologous pathway design in various model organisms and its integration with multistep biocatalysis …”
Section: Bioprocess Integrationmentioning
confidence: 99%
“…[13] Similarly,B ühler et al reported the use of heterologousp athway design in various model organisms and its integration with multistep biocatalysis. [14] In summary,m odification of the biocatalyst itself has proven its high potential to overcome certain underlying limitations of biocatalytic reaction systems. However, protein and metabolic engineering techniques cannot directly overcome given physicochemical properties, such as low solubilities of reactants within aqueous systems or undesired unfavorable thermodynamics, whichpreventh igh conversions.…”
Section: Introductionmentioning
confidence: 99%